2019
DOI: 10.17645/pag.v7i4.2216
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Democratic Tenets? Behavioural-Economic Imaginaries of a Future Food System

Abstract: This article makes the central argument that basic democratic values such as justice, autonomy and participation run the risk of being neglected when designing ‘nudges’ (i.e., indirect suggestions to influence individual behaviour) for sustainable behaviour change in the context of food governance, potentially complicating a democratisation of the food system. ‘Nudges’ uphold freedom of choice while simultaneously advocating a non-coercive soft force of paternalism to help people realise their preferences, max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The concept of justice is similar to fairness, which is associated with many alternative food networks and supply chains such as Fairtrade [245,246]. Other scholars addressed the concepts of "food democracy" [261,262,268,[270][271][272][273][274][275][276] or "food sovereignty" [261,[277][278][279][280][281][282][283], which are strongly linked to the way the food system is governed and managed and the inclusion of the different concerned stakeholders in the process of decision making about the future of agri-food systems, especially at the local level. Food democracy is a process that puts people at the center of and gives them a voice in and control over the transition towards more sustainable agri-food systems [270,271].…”
Section: Society and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The concept of justice is similar to fairness, which is associated with many alternative food networks and supply chains such as Fairtrade [245,246]. Other scholars addressed the concepts of "food democracy" [261,262,268,[270][271][272][273][274][275][276] or "food sovereignty" [261,[277][278][279][280][281][282][283], which are strongly linked to the way the food system is governed and managed and the inclusion of the different concerned stakeholders in the process of decision making about the future of agri-food systems, especially at the local level. Food democracy is a process that puts people at the center of and gives them a voice in and control over the transition towards more sustainable agri-food systems [270,271].…”
Section: Society and Culturementioning
confidence: 99%
“…These multi-stakeholder groups include food (policy) councils [274,368,[377][378][379][380][381][382], networks [281,344,383], and partnerships [384,385]. The innovative governance mechanisms allow increasing the participation and inclusion of stakeholders in managing food systems, thus democratizing it [261,262,268,[270][271][272][273][274][275][276]. In this regard, Béné et al [386] suggested that "To operationalize the great food system transformation and ensure its sustainability, five areas of research and action require more attention: economic and structural costs; political economy; diversity of cultural norms; equity and social justice; and governance and decision support tools".…”
Section: Policy and Governancementioning
confidence: 99%
“…They are designed to modify agents' behaviour at a least cost, through a mere presentation of different situations without modifying the choice set and without economic incentives (Thaler and Sunstein 2008). Recent research in sociology has, however, shown the limits of such approaches as well as the socially contrasted effects of a policy targeting only behaviour (Dubuisson-Quellier 2016;Wahlen and Dubuisson-Quellier 2018;Gumbert 2019).…”
Section: Processes and Drivers Of Change In Food Consumptionmentioning
confidence: 99%
“…Government policy is certainly not the most obvious thing that comes to mind when one thinks of empowerment. On the contrary, classical command-and-control policies (e.g., food safety regulations), economic incentives (e.g., 'fat taxes'), and also newer types of 'nudging' (such as food labels or food 'traffic light' ratings) are often under suspicion of infringing upon people's autonomy and approving rather than problematising established asymmetrical power relations between the state, food corporations and citizens (Gumbert, 2019;Mazzocchi et al, 2015). In fact, government policies addressing individual consumers are regularly criticised for violating the principle of consumer sovereignty (Korthals, 2001), hence disempowering and paternalizing individuals.…”
Section: Government Food Education Policymentioning
confidence: 99%